2022
DOI: 10.1080/15548627.2021.2016004
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3and carbamazepine protect againstClostridioides difficileinfection in mice by restoring macrophage lysosome acidification

Abstract: Clostridioides difficile infection (CDI) is a common cause of nosocomial diarrhea. TcdB is a major C. difficile exotoxin that activates macrophages to promote inflammation and epithelial damage. Lysosome impairment is a known trigger for inflammation. Herein, we hypothesize that TcdB could impair macrophage lysosomal function to mediate inflammation during CDI. Effects of TcdB on lysosomal function and the downstream pro-inflammatory SQSTM1/p62-NFKB (nuclear factor kappa B) si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Next, to directly determine the relationship between LIP levels and V-ATPase function, we tested the labile iron in HK2 cells after GD-R, with or without carbamazepine (CBZ), a lysosomal acidi cation activator which can restore V-ATPase function (29). As expected, CBZ improved lysosomal acidi cation after GD-R, con rming the restoration of V-ATPase function after treatment of CBZ (Figure 2I and 2J).…”
Section: Gd-r Elevates Lysosomal Ph and Inhibits The Assembly And Fun...supporting
confidence: 52%
“…Next, to directly determine the relationship between LIP levels and V-ATPase function, we tested the labile iron in HK2 cells after GD-R, with or without carbamazepine (CBZ), a lysosomal acidi cation activator which can restore V-ATPase function (29). As expected, CBZ improved lysosomal acidi cation after GD-R, con rming the restoration of V-ATPase function after treatment of CBZ (Figure 2I and 2J).…”
Section: Gd-r Elevates Lysosomal Ph and Inhibits The Assembly And Fun...supporting
confidence: 52%
“…TcdB is an exotoxin of Clostridioides difficile, which induces macrophage inflammation and epithelial damage, and destroys the normal function of lysosomes in macrophages. TcdB inhibits CTNNB1/β-catenin activity and lysosomal acidification in macrophages; the resulting lysosomal dysfunction affects the inflammatory response and causes tissue damage through autophagy [ 31 ]. It has been reported that mutations at the upper site of CTNNB1 are associated with tuberculosis caused by a conjugated divergent bacterium; this study also showed that CTNNB1 can affect host susceptibility to a conjugated divergent bacterium and this can be used as a marker gene to identify tuberculosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…However it is also an immunosuppressant and may increase a risk of infection for the old people. Carbamazepine an mTOR (mechanistic target of rapamycin kinase)-independent autophagy stimulator, prevented the compromised autophagic flux in septic mouse liver (Lin et al, 2014 ) and restored the mitophagic flux caused by a decline in lysosomal acidification (Ebrahimi-Fakhari et al, 2016 ; Chan et al, 2022 ). However, it is an antiepileptic drug and may not be applicable to all AD patients.…”
Section: Lysosomal Overloading Hypothesismentioning
confidence: 99%
“…Vitamins may also be supplied in the ketogenic diet. Vitamin D 3 (VD 3 ) promoted lysosomal degradation through inducing the nuclear translocation of PDIA3 (protein disulfide isomerase family A member 3) - STAT3 (signal transducer and activator of transcription 3) protein-complex and up-regulated the MCOLN3 (mucolipin 3) channel subsequently, which resulted in Ca 2+ releasing from the lysosome and the normal lysosomal acidification (Hu et al, 2019 ; Chan et al, 2022 ). VD 3 and VE and their combination improved memory and learning deficit, and decreased neuronal loss and oxidative stress in a rat model of AD (Mehrabadi and Sadr, 2020 ).…”
Section: Dietary Therapy Hypothesismentioning
confidence: 99%